Suppressive effects of saponin-enriched extracts from quinoa on 3T3-L1 adipocyte differentiation. Issue 10 (5th August 2015) - Yao, Yang; Zhu, Yingying; Gao, Yue; Shi, Zhenxing; Hu, Yibo; Ren, Guixing
Abstract : This study was performed to investigate the effect of quinoa saponins (QS) on the differentiation of 3T3-L1 preadipocytes. Abstract : This study was performed to investigate the effect of quinoa saponins (QS) on the differentiation of 3T3-L1 preadipocytes. QS inhibited triglyceride (TG) accumulation in the mature adipocytes, evidenced by oil-red O staining and intracellular quantification. Real time-PCR analysis and western blot analysis showed that QS significantly down-regulated the mRNA and protein expression of key adipogenic transcription factors, peroxisome proliferator-activated receptor γ (PPARγ), and CCAAT/enhancer-binding protein alpha (C/EBPα), however, they had no significant effect on CCAAT/enhancer-binding protein beta (C/EBPβ) and CCAAT/enhancer-binding protein delta (C/EBPδ) which are the upstream regulators for adipogenesis compared with mature adipocytes. QS also reduced mRNA and protein expression of sterol regulatory element-binding protein-1c (SREBP-1c) related to the late stage of adipogenesis. Furthermore, lipoprotein lipase (LPL), adipocyte protein 2 (aP2) and glucose transporter 4 (Glut4), as adipocyte specific genes, were decreased in mature adipocytes by QS treatment. These findings indicate that QS are capable of suppressing adipogenesis and therefore they seem to be natural bioactive factors effective in adipose tissue mass modulation.